Effects of Therapeutic Ultrasound Applied to the Lumbar Region on Renal Function: A Randomized Controlled Prospective Trial. (23rd January 2020) - Mengi, Alper; Ozdolap, Senay; Koksal, Tugce; Kokturk, Furuzan; Can, Murat; Sarikaya, Selda
Abstract : Objectives: Therapeutic ultrasound (TUS) is one of the most commonly used modalities in low back pain treatment. The objective of this study was to determine whether TUS applied to the low back region in patients with chronic low back pain had any effect on renal function. Methods: Forty patients with chronic low back pain were randomized to 2 groups by a block randomization method. Thirty‐seven patients completed the final evaluation. All patients were treated for 5 sessions per week for 3 weeks with the same physiotherapy modalities (superficial heating and transcutaneous electrical nerve stimulation) and exercise therapy; in addition to these treatments, the second group was treated with TUS for 10 minutes (frequency, 1 MHz; intensity, 1.5 W/cm 2 ; and effective irradiation area of the transducer head, 5 cm 2 ). The serum creatinine, serum cystatin C, 24‐hour urine creatinine, creatinine clearance, 24‐hour urine microalbumin and microprotein, urine volume, and glomerular filtration rate were measured. The patients were evaluated at baseline (day 0) and the end of the treatment (day 21). Results: The serum cystatin C levels were increased in both groups, but this increase was not significant ( P  > .05). There was no difference between the groups in the percent change in all outcome measures ( P  > .05). Conclusions: This showed that TUS applied to the low back region does not affect renal function.